Site-specific characterization and quantitation of N-glycopeptides in PKM2 knockout breast cancer cells using DiLeu isobaric tags enabled by electron-transfer/higher-energy collision dissociation (EThcD). Issue 11 (24th April 2018) - Chen, Zhengwei; Yu, Qing; Hao, Ling; Liu, Fabao; Johnson, Jillian; Tian, Zichuan; Kao, W. John; Xu, Wei; Li, Lingjun
Abstract : A multi-faceted site-specific quantitative N -glycoproteomics workflow was developed to probe PKM2 signaling. Abstract : The system-wide site-specific analysis of intact glycopeptides is crucial for understanding the exact functional relevance of protein glycosylation. A dedicated workflow with the capability to simultaneously characterize and quantify intact glycopeptides in a site-specific and high-throughput manner is essential to reveal specific glycosylation alteration patterns in complex biological systems. In this study, an enhanced, dedicated, large-scale site-specific quantitative N -glycoproteomics workflow has been established, which includes improved specific extraction of membrane-bound glycoproteins using the filter aided sample preparation (FASP) method, enhanced enrichment of N -glycopeptides using sequential hydrophilic interaction liquid chromatography (HILIC) and multi-lectin affinity (MLA) enrichment, site-specific N -glycopeptide characterization enabled by EThcD, relative quantitation utilizing isobaric N, N -dimethyl leucine (DiLeu) tags and automated FDR-based large-scale data analysis by Byonic. For the first time, our study shows that HILIC complements to a very large extent to MLA enrichment with only 20% overlapping in enriching intact N -glycopeptides. When applying the developed workflow to site-specific N -glycoproteome study in PANC1 cells, we were able to identify 1067 intact N -glycopeptides, representing 311 glycosylation sites and 88 glycan compositions from 205 glycoproteins. We further applied this approach to study the glycosylation alterations in PKM2 knockout cells vs. parental breast cancer cells and revealed altered N -glycoprotein/ N -glycopeptide patterns and very different glycosylation microheterogeneity for different types of glycans. To obtain a more comprehensive map of glycoprotein alterations, N -glycopeptides after treatment with PNGase F were also analyzed. A total of 484 deglycosylated peptides were quantified, among which 81 deglycosylated peptides from 70 glycoproteins showed significant changes. KEGG pathway analysis revealed that the PI3K/Akt signaling pathway was highly enriched, which provided evidence to support the previous finding that PKM2 knockdown cancer cells rely on activation of Akt for their survival. With glycosylation being one of the most important signaling modulators, our results provide additional evidence that signaling pathways are closely regulated by metabolism.